Development of an Osmium Redox Polymer Mediated Bioanode and Examination of its Performance in Gluconobacter oxydans Based Microbial Fuel Cell. Issue 6 (4th January 2017) - Aslan, Sema; Conghaile, Peter Ó; Leech, Dónal; Gorton, Lo; Timur, Suna; Anik, Ulku
Abstract: Gluconobacter oxydans ( G. oxydans ) cells together with an osmium redox polymer (ORP) [Osmium (2, 2'‐bipyridine)2(poly‐vinylimidazole)10Cl]Cl were combined with a glassy carbon paste electrode (GCPE) to form a bioanode for a microbial fuel cell (MFC) based on G. oxydans . Although there are G.oxydans / ORP combined bioanode in the literature, as far as it is known, this system is the first one where G.oxydans /ORP bioanode is combined with a cathode and a MFC is formed. After the optimization of experimental parameters, analytical characteristics of ORP/ G. oxydans /GCPE bioanode were investigated. ORP/ G. oxydans /GCPE showed two linear ranges for ethanol substrate as 1.0–30 mM (R 2 =0.902) and 30–500 mM (R 2 =0.997) and analytical range as 1.0–1000 mM. Limit of detection (3.0 s/m) and limit of quantification (10 s/m) values were calculated as 1.29 mM and 4.30 mM respectively where the RSD value was 1.16 % for n=5. Combining the developed bioanode in the presence of 5.0 mM K3 Fe(CN)6 mediator with a Pt wire cathode a double compartment MFC was obtained via a salt bridge. G. oxydans /GCPE bioanode based MFC had maximum power density of 0.133 μW cm −2 (at 33.5 mV), maximum current density as 8.73 μA cm −2 and OCP value of 156 mV. On the other hand, ORP/ G. oxydans /GCPE based MFC showed maximum power density as 0.26 μW cm −2 (at 46.8 mV), maximum current density as 15.079 μA cm ‐2 and OCP value of 176 mV. Abstract :